Test of Lepton-Flavor Universality in B→K∗ℓ+ℓ− Decays at Belle - Wehle, S.; Adachi, I.; Adamczyk, K.; Aihara, H.; Asner, D. M.; Atmacan, H.; Aulchenko, V.; Aushev, T.; Ayad, R.; Babu, V.; Behera, P.; Berger, M.; et al. (Physical review letters, 2021)
We present a measurement of R_{K^{*}}, the branching fraction ratio B(B→K^{*}μ^{+}μ^{-})/B(B→K^{*}e^{+}e^{-}), for both charged and neutral B mesons. The ratio for the charged case R_{K^{*+}} is the first measurement ever performed. In addition, we report absolute branching fractions for the individual modes in bins of the squared dilepton invariant mass q^{2}. The analysis is based on a data sample of 711  fb^{-1}, containing 772×10^{6}  BB[over ¯] events, recorded at the ϒ(4S) resonance with the Belle detector at the KEKB asymmetric-energy e^{+}e^{-} collider. The obtained results are consistent with standard model expectations.